Nitrous oxide abuse unmasking anti-phospholipid syndrome in a 24-year-old male with cerebral venous thrombosis and pulmonary thromboembolism: a case report - Sojung Yoon; Dong Yu Kim; Min Kyung Chu (BMC Neurology)
Abstract Background The abuse of nitrous oxide (N2O) as a recreational drug has become a growing concern, manifesting in various medical complications. Here, we report the first Korean case of cerebral venous thrombosis (CVT) and pulmonary thromboembolism (PTE) caused by nitrous oxide abuse and anti-phospholipid syndrome. Case presentation A 24-year-old Korean man studying abroad in the USA presented to the emergency department with altered sensorium, gait disturbance, and involuntary leg movements. His history revealed escalating nitrous oxide inhalation from occasional use to daily intake of 100 balloons over six months. The patient’s symptoms were initially attributed to cobalamin deficiency due to N2O abuse, leading to hyperhomocysteinemia and subsequent venous thrombosis, particularly CVT and PTE. However, the presence of Lupus Anticoagulant (LA) indicated a potential autoimmune or inflammatory process contributing to thrombotic complications, complicating the diagnosis. The patient’s treatment involved cobalamin supplementation, anticoagulation therapy, and addressing associated substance abuse and depression. Notably, subsequent tests revealed persistent positive LA, highlighting the complexity of the case and the multifactorial nature of N2O-induced complications. Conclusions The mechanisms underlying N2O-induced thrombotic complications are elucidated, primarily involving the oxidation of cobalamin to its inactive form, leading to hyperhomocysteinemia and endothelial dysfunction. The association with LA suggests a potential autoimmune or inflammatory component, adding another layer of complexity to pathophysiology. This case underscores the importance of recognizing and managing the systemic thrombotic risk associated with N2O abuse. It highlights the need for heightened vigilance in diagnosing and managing associated complications, including CVT, and emphasizes the importance of comprehensive diagnostic and treatment approaches addressing both medical and psychiatric aspects. In conclusion, this case serves as a poignant reminder of the serious medical consequences of N2O abuse and underscores the importance of early recognition, comprehensive management, and ongoing surveillance to mitigate its adverse effects on individual health and public well-being.